2019
DOI: 10.1007/s00520-019-05177-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of cryocompression as a method of enhanced limb hypothermia to reduce taxane-induced peripheral neuropathy

Abstract: Purpose Severe peripheral neuropathy is a common dose-limiting toxicity of taxane chemotherapy, with no effective treatment. Frozen gloves have shown to reduce the severity of neuropathy in several studies but comes with the incidence of undesired side effects such as cold intolerance and frostbite in extreme cases. A device with thermoregulatory features which can safely deliver tolerable amounts of cooling while ensuring efficacy is required to overcome the deficiencies of frozen gloves. The role of continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 26 publications
(39 reference statements)
1
36
0
Order By: Relevance
“…20 Another trial assessing nerve conduction demonstrated that cryocompression preserved motor amplitudes at 3 months. 26 Conversely, several studies included in this review reported that cryotherapy was not beneficial for the prevention of CIPN. 16,18,22,24 Both Beijers et al and Ruddy et al indicated no important differences in change of EORTC QLQ-CIPN20 scores.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…20 Another trial assessing nerve conduction demonstrated that cryocompression preserved motor amplitudes at 3 months. 26 Conversely, several studies included in this review reported that cryotherapy was not beneficial for the prevention of CIPN. 16,18,22,24 Both Beijers et al and Ruddy et al indicated no important differences in change of EORTC QLQ-CIPN20 scores.…”
Section: Discussionmentioning
confidence: 89%
“…20 Another trial assessing nerve conduction demonstrated that cryocompression preserved motor amplitudes at 3 months. 26…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations